Transcriptional switching of host defence response to combat hemibiotrophic fungal infection - Abdullah, Siti Nor A.; A. Bahari, Mohammad Nazri; M. Sakeh, Nurshafika (Wiley, 2022)
Hemibiotrophic fungal pathogens cause major destruction to food and industrial crops globally. Their dual infection phases appear to be a winning strategy. The pathogen establishes an initial colonisation biotrophically keeping the host cells alive. It then shifts to the notorious necrotrophic mode of infection, killing the host cells resulting in biochemical and physiological impairment destructive to the whole plant. A better understanding of the molecular interaction at the early stage of infection is critical to save the infected crops. In this article, we integrate findings from different plant–pathogen pathosystems to provide a comprehensive evaluation about the defence response network, covering crops that are infected through the aerial and root tissues. The high-throughput transcriptomics and metabolomics approaches as well as relevant biochemical and physiological analyses have revealed key genes and cellular components associated with signalling pathways and defence responses during the biotrophic and necrotrophic phases. Factors influencing the biotrophy to necrotrophy transition are discussed. Transcriptional reprogramming involving key regulatory proteins acting as master or key transcription factors to provide an effective two-stage defence network in host plants is also elaborated.